Molecular Phylogeny of rDNA-ITS on Native Dendrobium in Lampung - Mahfut, Mahfut; Syarif, Admi; Wahyuningsih, Sri (Journal of Multidisciplinary Applied Natural Science, 2025)
Dendrobium, a flagship collection of the Liwa Botanical Garden, is an endemic flora of the Southern Sumatra that requires preservation. One of the challenges in its conservation and potential development is the molecular identification. This molecular identification utilizes DNA barcoding with the rDNA-ITS marker as a practical, rapid, accurate, effective, and efficient alternative, complementing previous species-level identification results based on morphological characteristics. Amplification results from 5 selected samples showed specific bands measuring 300 bp. Sequence data analysis using BioEdit and MEGA V.11.0.11 software with 1000 bootstraps grouped all accessions into the same main cluster with a similarity range of 94–100%. Phylogenetic analysis revealed that accession D2 is similar to D. signatum from Japan (AB593662.1), and accession D3 to D. densiflorum (HQ114255), D4 to D. nobile (LC011413.1), accession D6 to D. trigonopus (KF143730.1), and accession D12 to D. faciferum (LC192955.1) from China. The results of this study will enrich the taxonomic and phylogenetic data of Dendrobium, which is essential for conservation and serves as a foundation for its development as a medicinal herbal plant.